2014
DOI: 10.1002/aqc.2453
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of two freshwater invasive macroinvertebrates, Procambarus clarkii and Physella acuta, by off‐road vehicles

Abstract: The red swamp crayfish (Procambarus clarkii) and the bladder snail (Physella acuta) are two invasive aquatic macroinvertebrate species with worldwide distribution that are plagues in rice fields.The purpose of this study was to investigate the possibility of accidental human dispersal of these two species by off‐road vehicles.An experimental approach was used owing to the difficulty of obtaining field data on low‐probability events such as passive dispersal. Experiments were performed testing the probability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Similarly, Waterkeyn et al . () observed the successful emergence of large numbers of invertebrates from mud collected from footwear and motor vehicles used in fieldwork at the Camargue, while Banha, Marques & Anastácio () observed that two invasive freshwater macroinvertebrates, the red swamp crayfish ad the snail Physella acuta (Physidae), can be transported in mud adhering to off‐road vehicles. These studies indicate that mud contributes to the adherence, continued attachment and survival of dispersal units.…”
Section: Requirements For Successful Bird‐mediated Ectozoochorous Dismentioning
confidence: 99%
“…Similarly, Waterkeyn et al . () observed the successful emergence of large numbers of invertebrates from mud collected from footwear and motor vehicles used in fieldwork at the Camargue, while Banha, Marques & Anastácio () observed that two invasive freshwater macroinvertebrates, the red swamp crayfish ad the snail Physella acuta (Physidae), can be transported in mud adhering to off‐road vehicles. These studies indicate that mud contributes to the adherence, continued attachment and survival of dispersal units.…”
Section: Requirements For Successful Bird‐mediated Ectozoochorous Dismentioning
confidence: 99%
“…Knowledge of dispersal mechanisms is very important for the management of species invasions, allowing their prevention by acting upon vectors (Crooks and Soulé, ; Bohonak and Jenkins, ; Banha et al, ). Hence, it is essential to gather information on freshwater anglers' activities, such as the use of live bait, movements, types of gear used, and fish species preference, which may affect accidental and intentional introductions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, bivalves adhering to birds via the 'grip' of their closed gape, may release when brought into contact with freshwater by a vectorbird. For example, Banha et al (2014) observed that non-native snails (Pysella acuta) maintained attachment to a human vector (offroad vehicle) for circa 100 km, and subsequent detachment was promoted by contact with freshwater. Moreover, many waterbird species will often preen and wash themselves with freshwater, which may facilitate detachment of plumage enmeshed bivalves in a suitable environment.…”
Section: Post Dispersalmentioning
confidence: 99%